TRENDS AND DEVELOPMENTS IN INTELLIGENT AGENT FOR SOCIALLY SHARED REGULATED LEARNING (SSRL): A BIBLIOMETRIC REVIEW - Alias, Asmara; Saad, Aslina; Ariffin, Asma Hanee; Fahri, Hafizul (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The integration of intelligent agents in supporting Socially Shared Regulation of Learning (SSRL) has gained significant scholarly interest in recent years, aligning with the broader evolution of Artificial Intelligence (AI) in education. Despite its growing relevance, a comprehensive understanding of research trends, influential contributions, and thematic developments within this niche remains limited. This study aims to address that gap by conducting a bibliometric analysis titled “Trends and Developments in Intelligent Agent for Socially Shared Regulated Learning (SSRL),” using a dataset of 1951 publications retrieved from the Scopus database. Employing Scopus Analyzer, OpenRefine, and VOSviewer software, we systematically examined publication output, citation patterns, country contributions, author impact, keyword co-occurrences, and collaboration networks spanning from 1983 to 2025. The analysis revealed a sharp increase in publication volume post-2010, with peak activity occurring between 2010 and 2023, driven predominantly by contributions from the United States, the United Kingdom, China, and Canada. Keyword clustering highlighted dominant themes, including metacognitive support, agent-based learning systems, collaborative regulation, and AI-driven feedback mechanisms. Furthermore, the co-authorship and institutional analysis demonstrated an emerging but fragmented research community, suggesting opportunities for enhanced international collaboration. The findings map the intellectual landscape of intelligent agents in SSRL and provide actionable insights for future research. It highlights areas with high potential for interdisciplinary integration and technological innovation. This study provides a foundational perspective for researchers, policymakers, and developers seeking to leverage intelligent agents in fostering effective collaborative learning environments.